2017
DOI: 10.1039/c7ra03845c
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid eutectic mixtures and derivatives from non-edible animal fat as phase change materials

Abstract: Non-edible animal fat waste as a source of phase change materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Additionally, this extraction methodology allows the reuse of the biocatalyst. whereas the latter presented the best selectivity towards diol moiety formation (3.40 ppm, m, H-COH) [4].…”
Section: Bio-catalytic Preparation Of Dhses: Esters From Methanol To mentioning
confidence: 98%
See 3 more Smart Citations
“…Additionally, this extraction methodology allows the reuse of the biocatalyst. whereas the latter presented the best selectivity towards diol moiety formation (3.40 ppm, m, H-COH) [4].…”
Section: Bio-catalytic Preparation Of Dhses: Esters From Methanol To mentioning
confidence: 98%
“…However, the melting temperatures of these four alcoxyl stearates were nearly 30 ºC lower than their DHSE counterparts. Indeed, to prepare stearates as On the other hand, some of the described commercial fatty acid bio-based PCMs [11,12,14] and the bio-based eutectic mixture from non-edible animal fat prepared by some of the authors [4] presented latent heats of solidification ranging 150 kJ•kg -1 [11,12,14] to 180 kJ•kg -1 [4].…”
Section: Thermal Properties and Cycling Reliability Of The Dhses Frommentioning
confidence: 99%
See 2 more Smart Citations
“…However, the melting temperature of single fatty acids is high and sometimes difficult to meet the practical application requirement. It is found that the melting temperature can be lowered down to an appropriate value by mixing two or more than two kinds of fatty acid to produce a binary or polynary eutectic mixture . Apart from fatty acids, saturated alcohols are also a kind of important phase change material and have also been widely studied as PCM .…”
Section: Introductionmentioning
confidence: 99%